Enhancing Collaboration and Learning Outcomes through the Jigsaw Cooperative Learning Model among Elementary School Students - Putri, Dina Eliarto; Pratiwi, Siska (Universitas of Muhammadiyah Makassar, 2025)
Low academic achievement and limited collaborative interaction remain prevalent challenges in primary education learning processes. Conventional teacher-centered approaches have been insufficient in fostering active participation and student cooperation. This study aims to analyze the impact of the Jigsaw cooperative learning model on improving learning outcomes and collaboration among elementary school students. Employing a quantitative approach with a one-group pretest-posttest pre-experimental design, the study involved 23 third-grade students from UPTD SDN Lajing 5 Arosbaya. The instruments used included a learning achievement test and a student collaboration questionnaire. Data were analyzed through validity, reliability, normality tests, and the Paired Sample T-Test using SPSS v21.0. The findings indicate a significant improvement in both academic performance and student cooperation following the implementation of the Jigsaw model. Post-test scores and collaboration indicators increased substantially, with a significance value of 0.000 (p 0.05). The instruments were found to be valid and reliable, with normally distributed data. In conclusion, the Jigsaw model proved effective in enhancing both learning outcomes and student collaboration in primary education. This study contributes empirical evidence supporting the Jigsaw method's efficacy in the context of Pancasila Education and recommends it as an innovative strategy for fostering active and collaborative learning.